Increased jejunal permeability in human obesity is revealed by a lipid challenge and is linked to inflammation and type 2 diabetes. Issue 2 (28th August 2018) - Genser, Laurent; Aguanno, Doriane; Soula, Hédi A; Dong, Liping; Trystram, Laurence; Assmann, Karen; Salem, Joe‐Elie; Vaillant, Jean‐Christophe; Oppert, Jean‐Michel; Laugerette, Fabienne; Michalski, Marie‐Caroline; Wind, Philippe; et al.
Abstract: Obesity and its metabolic complications are characterized by subclinical systemic and tissue inflammation. In rodent models of obesity, inflammation and metabolic impairments are linked with intestinal barrier damage. However, whether intestinal permeability is altered in human obesity remains to be investigated. In a cohort of 122 severely obese and non‐obese patients, we analyzed intestinal barrier function combining in vivo and ex vivo investigations. We found tight junction impairments in the jejunal epithelium of obese patients, evidenced by a reduction of occludin and tricellulin. Serum levels of zonulin and LPS binding protein, two markers usually associated with intestinal barrier alterations, were also increased in obese patients. Intestinal permeability per se was assessed in vivo by quantification of urinary lactitol/mannitol (L/M) and measured directly ex vivo on jejunal samples in Ussing chambers. In the fasting condition, L/M ratio and jejunal permeability were not significantly different between obese and non‐obese patients, but high jejunal permeability to small molecules (0.4 kDa) was associated with systemic inflammation within the obese cohort. Altogether, these results suggest that intestinal barrier function is subtly compromised in obese patients. We thus tested whether this barrier impairment could be exacerbated by dietary lipids. To this end, we challenged jejunal samples with lipid micelles and showed that a single exposure increased permeability to macromolecules (4 kDa). Jejunal permeability after the lipid load was two‐fold higher in obese patients compared to non‐obese controls and correlated with systemic and intestinal inflammation. Moreover, lipid‐induced permeability was an explicative variable of type 2 diabetes. In conclusion, intestinal barrier defects are present in human severe obesity and exacerbated by a lipid challenge. This paves the way to the development of novel therapeutic approaches to modulate intestinal barrier function or personalize nutrition therapy to decrease lipid‐induced jejunal leakage in metabolic diseases. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.